Reformasi Birokrasi dalam Upaya Pemberantasan Korupsi di Kabupaten Batang (Kepemimpinan Yoyok Riyo Sudibyo, Periode 2012 – 2017) - Mashun Mukromin Ahmad; Teguh Yuwono; Neny Marlina (Journal of Politic and Government Studies, 2017)
Bureaucracy reform is an attempt to reform and change the governance system that concerns the aspects of human resources and work procedures. The spirit of reform is basically contained in the vision of Batang District "Realization of Effective, Clean, Professional Government". Implementation of this bureaucratic reform, is expected to realize an effective, clean and professional government to eradicate corruption in the area of Government Batang District The research method used is qualitative approach with data collection technique that is observation, interview and document. Informants or resource persons in this research are Bupati, Sekda, Head of BKD, Assistant 3, Section Organization, Disdukcapil, BPMPT, and five people of Batang District public service users. The results showed that bureaucratic reforms conducted by the Batang regency government in order to eradicate corruption can be said to have been running well and successfully. During the period of Yoyok Riyo Sudibyo's leadership from 2012 - 2017, there is no data showing the occurrence of corruption cases in Batang District. During that period, Kabupaten Batang experienced many changes, ranging from work procedures, structure, behavior, and old habits in the bureaucracy has been much better. Bureaucracy reform here is a gradual and continuous reform process that does not include radical and revolutionary efforts and / or actions. Recommendations for the Government of Batang Regency namely the government system that has been established by the Regent Yoyok Riyo Sudibyo is good, need to be continued and improved again and maintained by various parties, government, private, and community. Then it is necessary to improve the capacity and quality of human resources, especially the quality of bureaucracy in order to always be able to support the realization of effective, clean, professional sustainable governance. Keywords : Bureaucracy reform, corruption